Musée de Bruxelles. Teniers (David) (1610-1690). Le Médecin de Village... - Teniers | David | II (Wikimedia Commons)
Notice image issue de Wikimedia Commons. Titre: Musée de Bruxelles. Teniers (David) (1610-1690). Le Médecin de Village - The Village doctor, GP019314. Title Musée de Bruxelles. Teniers (David) (1610-1690). Le Médecin de Village - The Village doctor Contributor Teniers, David, II (Flemish painter and etcher, 1610-1690) (author original work) Date [date de publication inconnu] Publisher [lieu de publication inconnu]: Nels Uniform title Bruxelles-Brussel. Beelden en objecten. Koninklijke Musea voor Schone Kunsten van België Series Belgique. Région de Bruxelles-Capitale. Cartes postales Belgium. Brussels-Capital Region. Postcards België. Brussels Hoofdstedelijk Gewest. Prentkaarten Genre Post cards Extent 1 kaart / postcard Graphic Brown Language French Additional info General note: Museum van Brussel. David Teniers (1610-1690). De Dorpsheelmeester General note: Titelgegevens ontleend aan prentkaart Source Library Catalog Source ID lbsn9992295051601471
Droits : Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; Patrimoine; architecture; Histoire Locale; Carte postale